Upaya Badan Pemberdayaan Perempuan dan Keluarga Berencana (Bppkb) dalam Penanggulangan Kasus Kekerasan Anak Dan Perempuan Di Kabupaten Kendal - Firdausi, Aulya Della; Susanti, Martien Herna; Sunarto, Sunarto (Unnes Political Science Journal, 2018)
The case of child and woman violence in Kendal District has increased for three consecutive years since 2013. One of the agencies responsible for the prevention of child and female violence cases in Kendal District is the Women's Empowerment and Family Planning Agency (BPPKB). So the the problem in this research are (1) How is the effort of BPPKB in handling child and woman violence case in Kendal District?, (2) What is the cooperation system of BPPKB with other institutions?, and (3) What kind of problems did BPPKB get in handling cases of child and woman violence in Kendal District?. The results of the research show (1) the effort that has been done by BPPKB in handling cases of child and woman violence can be divided into two, prevention and handling after the happening of the case. As a prevention, BPPKB has conducted socialization activities with the material of Law Number 23 Year 2002 regarding Child Protection and Law Number 23 Year 2004 on the Elimination of Domestic Violence. Then for the post-case handling, the victims will be given five services in the form of Reporting Service, Health Service, Advocacy Service, Rehabilitation Service by Shelter and lastly Service of Return and Social Reintegration. (2) Cooperation conducted by BPPKB with other institutions contained in the Decree of Regent of Kendal Number: 463/248/2012 then formed an Integrated Service Team on Handling of Violence Against Women Based on Gender and Child which then formed an organization of Center for Integrated Service of Handling of Violence of Women and Larasati Children (PPT - PKPA Larasati). (3) The problem faced by BPPKB is the lack of human resources and infrastructure facilities. The suggestions that can be given is the addition of the number of human resources officers in both the reporting service and medical services, increasing the intensity of socialization in various layers of society and maintaining cooperation relationship between BPPKB and various related agencies that work together.